2020
DOI: 10.1099/ijsem.0.004211
|View full text |Cite
|
Sign up to set email alerts
|

Gimesia chilikensis sp. nov., a haloalkali-tolerant planctomycete isolated from Chilika lagoon and emended description of the genus Gimesia

Abstract: A Gram-stain-negative, aerobic, non-motile, salt- and alkali-tolerant, pear to oval shaped, rosette-forming, white coloured, bacterium, designated as strain JC646T, was isolated from a sediment sample collected from Chilika lagoon, India. Strain JC646T reproduced through budding, grew well at up to pH 9.0 and tolerated up to 7 % NaCl. Strain JC 646T utilized α-d-glucose, fumarate, lactose, sucrose, fructose, d Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Notably, our analysis shows that the two described species G. chilikensis (Kumar et al 2020) and G. benthica (Wang et al 2020) do not seem to belong to different species by the here applied measures. We must assume that this inconsistency derives from the fact that G. benthica was described only a few weeks after G. chilikensis-and therefore each of these studies only compared the new strain to G. maris, rather than to each other.…”
Section: Phylogenetic Inferencementioning
confidence: 65%
See 3 more Smart Citations
“…Notably, our analysis shows that the two described species G. chilikensis (Kumar et al 2020) and G. benthica (Wang et al 2020) do not seem to belong to different species by the here applied measures. We must assume that this inconsistency derives from the fact that G. benthica was described only a few weeks after G. chilikensis-and therefore each of these studies only compared the new strain to G. maris, rather than to each other.…”
Section: Phylogenetic Inferencementioning
confidence: 65%
“…While these features were also found in the recently described species Gimesia benthica (Wang et al 2020), they were however not identified in another recently described species of the genus, Gimesia chilikensis (Kumar et al 2020). While many Planctomycetes produce carotenoids as pigmenting compounds, probably for protection against UV radiation or oxidative stress (Kallscheuer et al 2019), the three previously described Gimesia species possess a white colony colour (Kumar et al 2020), indicating the inability to produce such pigments.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Maximum likelihood 16S rRNA gene sequence-based phylogeny was computed for the eight novel strains, the type strains of all recently described planctomycetal species (as of June 2020) (Kallscheuer et al 2020b;Kumar et al 2020;Peeters et al 2020;Rivas-Marin et al 2020a, b;Schubert et al 2020) and all isolates recently published, but not yet described (Wiegand et al 2020). The 16S rRNA gene sequences were aligned with SINA (Pruesse et al 2012).…”
Section: Construction Of Phylogenetic Trees For the Novel Isolatesmentioning
confidence: 99%